2010
DOI: 10.3748/wjg.v16.i37.4697
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of MMP7 serum levels in the diagnosis of cholangiocarcinoma

Abstract: Serum values of MMP7 and CA19-9 appear to be useful biomarkers for differentiating cholangiocarcinoma from benign biliary tract obstructive diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 27 publications
0
35
0
Order By: Relevance
“…MMP-7 has also been shown to activate other MMPs, such as pro-MMP-2 and pro-MMP-9, and to inhibit E-cadherin function by inducing ectodomain shedding of E-cadherin (23,24). The results of several recent studies have indicated that MMP-7 is overexpressed in a variety of epithelial cancers, including esophagus, colon, pancreas, and cholangiocarcinoma, and is associated with cancer progression (25)(26)(27)(28). Thus, the invasive capacity of CD24 + cells not only depends on their adherent capabilities but also on increased MMP-7 expression.…”
Section: Discussionmentioning
confidence: 97%
“…MMP-7 has also been shown to activate other MMPs, such as pro-MMP-2 and pro-MMP-9, and to inhibit E-cadherin function by inducing ectodomain shedding of E-cadherin (23,24). The results of several recent studies have indicated that MMP-7 is overexpressed in a variety of epithelial cancers, including esophagus, colon, pancreas, and cholangiocarcinoma, and is associated with cancer progression (25)(26)(27)(28). Thus, the invasive capacity of CD24 + cells not only depends on their adherent capabilities but also on increased MMP-7 expression.…”
Section: Discussionmentioning
confidence: 97%
“…Serum levels of MMP-7 are also elevated in CCA patients and have been suggested as a diagnostic biomarker for CCA [40]. For the discrimination between CCA patients and healthy controls, a diagnostic sensitivity of 75% with a specificity of 78% was described [41]. …”
Section: Resultsmentioning
confidence: 99%
“…The strongest evidence for such activity has been in vitro experiments concerning matrilysin (MMP-7) Vargo-Gogola et al (2002). MMP-7 has been found to be over-expressed in several tumors, such as those associated with esophageal, cholangiocarcinoma, gastric, colon, prostate and bladder cancer (Hashimoto et al,1998;Martinez-Fernandez et al, 2009;Leelawat et al, 2010;Yeh et al, 2010;Szarvas et al, 2011;Zhou et al, 2011). MMP-7 levels are included in the evaluation of cancer invasion and metastases.…”
Section: Introductionmentioning
confidence: 99%
“…Degradation by MMP-9 is required for both tumor invasion and metastases (Murray et al, 2004). Increased invasion and expression of MMP-9 in human colorectal lines by a CD44-dependent mechanism (Hashimoto et al, 1998;Murray et al, 2004;Martinez-Fernandez et al, 2009;Leelawat et al, 2010;Yeh et al, 2010;Szarvas et al, 2011).…”
Section: Introductionmentioning
confidence: 99%